Implementation of Simple Multi Attribute Rating Technique Method using Decision Support System Concept (Case Recommendation of Salon Place in Pematangsiantar City) - Rahadjeng, Indra Riyana; Windarto, Agus Perdana (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
The purpose of the research is to determine the ideal salon place considering the salon is a place visited by women to beautify themselves. This research can also be used as recommendations in the form of information in deciding whether consumers visit the salon or not based on research results. The method used in decision making is the SMART (Simple Multi Attribute Rating Technique) method. To determine the evaluation of the salon, researchers used 5 assessment criteria, among others: service (C1), facilities (C2), products (C3), price (C4) and Purchase Decision (C5). For alternatives used as a salon, among others: salon Sukim (A1), Necis (A2), Endah (A3), Crown (A4) and Chan Dhai (A5). The results obtained by Sukim (A1) with a final value of 0.8835 as the first rank, Endah Salon (A2) with a final score of 0.5530 as the second rank and Chan Dai (A5) with a final value of 0.45 as the third rank.